Acetic acid inhibition on methanogens in a two-phase anaerobic process - Ng, Wun Jern (2013)
The inhibitory effect of acetic acid on methanogens in a two-phase anaerobic process was evaluated. The results in this study showed that some methanogens still existed in the acidogenic phase although their dominance in the total microbial community was only 1% compared to 9.6% in the methanogenic phase. The inhibition threshold of acetic acid on acidogenic phase methanogens was, however, higher than that on methanogenic phase methanogens. At pH 6.00, acetic acid inhibition on methanogenic phase methanogens was observed when acetic acid concentration was higher than 1619.47 mg HAc/L although there was no obvious inhibition on acidogenic phase methanogens in the range of 1646.47–2781.19 mg HAc/L. There was also no acetic acid inhibition on acidogenic phase methanogens at pH 5.50, 6.00 and 6.50 in the range of 565.29–2781.19 mg HAc/L. However, for methanogenic phase methanogens, the inhibition was obvious and a second order substrate inhibition model, qs = qmS/[Ks + S + (S2/Ki)], could be adapted to describe the inhibition kinetics and mechanism of undissociated acetic acid on methanogenic phase methanogens. The results showed substrate saturation constant Ks, substrate inhibition constant Ki, and maximum specific utilization rate of acetic acid qm, were 1.66 mg unHAc/L, 145.17 mg unHAc/L, and 3.53 mg HAc/L g MLVSS h, respectively.